2016
DOI: 10.1007/s00586-016-4599-9
|View full text |Cite
|
Sign up to set email alerts
|

Six-month outcomes from a randomized controlled trial of minimally invasive SI joint fusion with triangular titanium implants vs conservative management

Abstract: Purpose To compare the safety and effectiveness of minimally invasive sacroiliac joint fusion (SIJF) using triangular titanium implants vs conservative management (CM) in patients with chronic sacroiliac joint (SIJ) pain. Methods 103 adults with chronic SIJ pain at nine sites in four European countries were randomly assigned to and underwent either minimally invasive SIJF using triangular titanium implants (N = 52) or CM (N = 51). CM was performed according to the European guidelines for the diagnosis and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 46 publications
2
80
2
2
Order By: Relevance
“…[8][9][10]41,42 Specifically, the TPS implants were found to exhibit a substantial degree of bone ongrowth and ingrowth to their surfaces, resulting in a mechanically stable interface with surrounding host bone. The AM implants investigated herein provide a highly interconnected porous surface with an open fenestrated core structure that offers comparatively greater surface area for bony integration and the ability to be pre-packed with graft material, which may benefit a number of spinal implants, such as fusion, disc, and SI joint implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10]41,42 Specifically, the TPS implants were found to exhibit a substantial degree of bone ongrowth and ingrowth to their surfaces, resulting in a mechanically stable interface with surrounding host bone. The AM implants investigated herein provide a highly interconnected porous surface with an open fenestrated core structure that offers comparatively greater surface area for bony integration and the ability to be pre-packed with graft material, which may benefit a number of spinal implants, such as fusion, disc, and SI joint implants.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective clinical trials [8][9][10] have shown high levels of pain relief and improvement in disability scores and quality of life in patients undergoing SI joint fusion with a series of titanium plasma spray (TPS) coated triangular implants placed transarticularly across the SI joint. Computed tomography scan follow-up in the two U.S. trials have shown high rates of bone adherence to implants and signs of bridging bone across the SI joint.…”
Section: Introductionmentioning
confidence: 99%
“…If the frequently used threshold of 15% is used, the average decrease of 18% provides evidence for the clinical relevance in our patient population in this area as well. If the end values for VAS and ODI 24 months following posterior fusion were compared with the results recently published by Sturesson et al [34] 6 months after lateral percutaneous stabilization, comparable values are yielded ( Table 4). According to Grafton [35], the minimum detectable change in the overall score of the SF-MPQ is 8.7%, which was reached here at an observed decrease of 19% in the values after a 24-month observation period.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, mean ODI decreased by only 4.6 points in the nonsurgical group. In the European randomized trial, 18 Mean pain scores improved in the SIJ fusion group from 77.7 at baseline to 34.4 at 6 months (a 43.3 point improvement p<.0001) vs. 73.0 to 67.8 (an improvement of 5.7 points, p=.1105) in the non-surgical group. ODI improved by 20 points more in the surgical vs. non-surgical groups 9p<.0001).…”
Section: Coverage Rationale For Open and Minimally Invasive Sij Fusionmentioning
confidence: 94%
“…17 Responses in the non-surgical arms of two prospective randomized trials showed little, if any, improvement at 6 months. 18,19 Given the absence of published outcomes data supporting long-term pain relief from non-surgical treatment, patients with a diagnosis of SIJ pain who experience pain for a minimum of six months and who do not respond to an adequate course of non-surgical treatment may be considered for SIJ fusion.…”
Section: Introductionmentioning
confidence: 99%